Developing the 4 S Instructional Model for the Dramatic Arts Strand 3 in the Learning Area of Art for Prathom Suksa 5 Students - Petsri, Wiwat (Ubon Ratchathani Journal of Research and Evaluation, 2018)
The purposes of this study were (1) to study and analyze baseline data to develop the 4 s Instructional model for the Dramatic Arts Strand 3 in the learning area of art for Prathom Suksa 5 students in Saritdidet school, (2) to create and develop 4 S learning management model and (3) to compare the students’ performance skills in Dramatic arts and their learning achievement before and after using the 4s Instructional model. The samples of this study was 50 Prathom Suksa 5/4 students in Saritdidet school, Muang Chanthaburi district, Chanthaburi province in the academic year of 2016 and was selected by using cluster random sampling. The instruments of this study consisted of lesson plans, a performance skills test, and a learning achievement test. The statistics used for data analysis were: mean and standard deviation. The research findings were as follows: 1. The developed 4 S instructional model was effective. The model consisted of theories and basic concepts, principles of modeling, objectives, processes and procedures of learning management, atmosphere, components of learning management, and measurement and evaluation. 2. The model was composed of 4 stages: Stage 1, Stimulus (presenting the stimulus); Stage 2,Start (preparation); Stage 3, Step (practice); and Stage 4, Star (presentation and evaluation, 3. The results of the comparison of the students’ performance skills in Dramatic arts and their learning achievement before and after using the 4S instructional model revealed that the post-test scores of the students’ performance skills in Dramatic arts and their learning achievement were higher than the pre-test scores. The pre-test scores of the students’ performance skills in Dramatic arts had an average of 11.52, and the post-test scores had an average of 17.01, The pre-test scores of their learning achievement had an average of 6.76, and the post-test scores had an average of 14.58.